‘Greed is good’ : a hard lesson to unlearn - J. Soedradjad Djiwandono (2014)
A recent survey about greed culture in Wall Street showed an alarming tendency: despite much effort by governments to strengthen regulation and supervision of finance, greed and corrupt practices might not be declining.